2020
DOI: 10.3389/frvir.2020.602299
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Analgesia for Children With Large Severe Burn Wounds During Burn Wound Debridement

Abstract: The objective of this study was to compare the effect of adjunctive virtual reality vs. standard analgesic pain medications during burn wound cleaning/debridement. Participants were predominantly Hispanic children aged 6–17 years of age, with large severe burn injuries (TBSA = 44%) reporting moderate or higher baseline pain during burn wound care. Using a randomized between-groups design, participants were randomly assigned to one of two groups, (a) the Control Group = pain medications only or (b) the VR Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 80 publications
(91 reference statements)
0
25
0
1
Order By: Relevance
“…Another limitation is that the current study is an analog laboratory pain study, with only brief thermal pain stimuli and brief VR treatment durations. Whether the current results generalize to clinical settings (e.g., severely burned children during 20 min burn wound debridement sessions) is an important research topic for future clinical studies with patients during painful medical procedures, e.g., 2 , 58 .…”
Section: Discussionmentioning
confidence: 94%
“…Another limitation is that the current study is an analog laboratory pain study, with only brief thermal pain stimuli and brief VR treatment durations. Whether the current results generalize to clinical settings (e.g., severely burned children during 20 min burn wound debridement sessions) is an important research topic for future clinical studies with patients during painful medical procedures, e.g., 2 , 58 .…”
Section: Discussionmentioning
confidence: 94%
“…When looked into different VR interventions, active VR yields medium to large effect sizes ranging from Cohen's d of 0.39 (Xiang et al, 2021) to 1.03 (Hoffman et al, 2019), which was similar to the studies using Multi-Modal Distraction (Cohen's d ranging from 0.4 to 1.72). VR was found to be effective in reducing self-reported pain when compared to standard distraction (e.g., TV, videos, books, and toys (Miller et al, 2011;Kipping et al, 2012;Brown et al, 2014)), as well as standard medication care (Hoffman et al, 2019;Hoffman et al, 2020).…”
Section: Meta-analysismentioning
confidence: 99%
“…Active VR refers to the VR games that involves interactions of the patients to the virtual environment. In Hoffman et al (2019Hoffman et al ( , 2020 and Jeffs et al (2014) studies, VR Snow World was adopted and found to be effective in alleviating pain during the wound care (Jeffs et al, 2014;Hoffman et al, 2019;Hoffman et al, 2020). The snowy VR environment was designed with special considerations given to pediatric burn patients.…”
Section: Vr Intervention and Exposurementioning
confidence: 99%
See 2 more Smart Citations